Relation between vitamin C and vitamin E levels with malondialdehyde in elderly - Prasetyastuti Sunarti, Dyah Arum Retnaningstyas Irianti Puji Lestari (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2007)
Background: Aging is a natural process during life. One of the aging theories is related to free radical production. Increase of free radical production can trigger lipid peroxidation that result in peroxide lipid such as malondialdehyde (MDA). The lipid peroxidation can be inhibited by body defence system such 8S vitamin C and vitamin E.ObJective: to understand the relation between plasma vitamin C, vitamin E and MDA levels in elderly Method: This was an observational research with cross sectional design. The subjects were thirty two elderly who live in Pakem district, Sleman. Determination of vitamin C and peroxide lipid level used spectrophotometer, whereas vitamin E level was determined by spectrofluorometer.Reaulta : The concentration of vitamin C , vitamin E and MDA of the subjects were 0.50 + 0.26 mglml, 26.38 ..:!:. 7.95 pg/ml and 0.23 ..:!:. 0.13 nmol/ml respectively. The correlation of both vitamin C vs MDA and vitamin E vs MDA were not significant, r = -0.012 and -0,108, respectively.Conclualon: There were no correlation between vitamin C, vitamin E and MDA levels.Keyword: elderly ; free radical;vitamin C; vitamin E; malondialdehyde.